The Effects of Use of the Range Extender in a Small Commercial Electric Vehicle - Marcin Noga; PaweÅ‚ Gorczyca; RadosÅ‚aw Hebda (Automotive Experiences, 2021)
Research on the effects of the use of the range extender developed for a small commercial electric vehicle was presented in this paper. The range extender has a maximum output power of 2.65 kW. The developed auxiliary power unit consists of a three-phase generator propelled by an industrial low-power spark-ignition engine. The exhaust system was improved using a more efficient muffler. The implemented motorcycle muffler has a three-way catalyst (TWC) integrated inside. The use of the more advanced exhaust system aimed at reducing noise and exhaust emissions of the range extender. The efficient operation of the three-way catalytic converter requires a stoichiometric air-fuel ratio. To enable desired air-fuel ratio a fuel system was modified. In the first stage of research, the effects of improvements of the exhaust system on the range extender noise emissions were quantified. The next step covered the research of the fuel conversion efficiency, the exhaust gas composition, and the efficiency of conversion of the three-way catalyst. A significant decrease of noise and toxic gas emissions and an increase in the fuel conversion efficiency were revealed. The mentioned research was conducted in stationary conditions. After that, in the final part research of the running vehicle with the range extender on was made. The beneficial outcome of these tests enabled the development of a set of rules of the control of the range extender.